Climate Change is a Bioethics Problem - Macpherson, Cheryl Cox (Bioethics, 2013)
Climate change harms health and damages and diminishes environmental resources. Gradually it will cause health systems to reduce services, standards of care, and opportunities to express patient autonomy. Prominent public health organizations are responding with preparedness, mitigation, and educational programs. The design and effectiveness of these programs, and of similar programs in other sectors, would be enhanced by greater understanding of the values and tradeoffs associated with activities and public policies that drive climate change. Bioethics could generate such understanding by exposing the harms and benefits in different cultural, socioeconomic, and geographic contexts, and through interdisciplinary risk assessments. Climate change is a bioethics problem because it harms everyone and involves health, values, and responsibilities. This article initiates dialog about the responsibility of bioethics to promote transparency and understanding of the social values and conflicts associated with climate change, and the actions and public policies that allow climate change to worsen.